The Influence of Fear of Missing Out on the Menstrual Cycles of Adolescent Girls - Agustina Mar'atus Sholichah; Ade Zakiya Tasman Munaf; Zahwa Nur Azizah Hakim; Arnasyifaa Asiyah Taqvia; Zulfa Tiara Agustina (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2026)
Social media has become the primary platform for adolescents, especially girls, to connect, express themselves, and obtain information. However, easy access often triggers Fear of Missing Out (FoMO), leading to constant use that increases stress and anxiety. Persistent stress interferes with hormones such as luteinizing hormone (LH) and follicle‑stimulating hormone (FSH), contributing to irregular menstrual cycles. This cross‑sectional analytical study at the Midwifery Department, Sutomo Campus, Poltekkes Kemenkes Surabaya, used simple random sampling among 215 first‑year students, with FoMO as the independent variable and menstrual cycle status as the dependent variable. FoMO was measured using the FoMO scale, cyclical patterns via questionnaire, and the data were analyzed using binary logistic regression. FoMO levels were categorized based on means and standard deviations; cycles were classified as normal or abnormal. Results showed that 58% of participants had high FoMO and 65.58% experienced abnormal cycles. Logistic regression revealed that higher FoMO was strongly associated with abnormal menstrual cycles (p < 0.001), with elevated FoMO carrying about 6.191 times greater odds of menstrual irregularity compared to lower FoMO. The findings support integrating psychosocial interventions into student health services, including routine FoMO screening and digital wellness workshops, to reduce menstrual disturbances and promote adolescent reproductive health in the digital age.